Thrombolytic therapy for acute extra-cranial artery dissection: report of two cases - Osama O. Zaidat; Jose Americo M. Fernandes Filho; Gurwant Singh; Jose I. Suarez (Arquivos de Neuro-Psiquiatria)
Extra-cranial arterial dissection accounts for 10% of strokes in young people. Information on safety of thrombolytic administration in this group is limited. The literature, however, does not favor use of thrombolytics for myocardial ischemia when peripheral arterial dissection coexists. Based on the clinical and radiological features, two patients who presented with acute stroke secondary to arterial dissection were considered for thrombolysis. One of them received intra-venous recombinant tissue plasminogen activator (rtPA), and the other patient received intra-arterial rtPA. There were no post thrombolysis complications. This report supports feasibility of administering thrombolytics in acute ischemic strokes resulting from extra-cranial arterial dissection. Future larger studies are necessary to determine the efficacy, safety and long-term outcome in this patient population.